Acidic pH and thiol-driven homogeneous cathodic electrochemiluminescence strategy for determining the residue of organophosphorus pesticide in Chinese cabbage. (1st November 2022) - Yang, Qiaoting; Zhao, Suixin; Li, Haiyin; Li, Feng
Highlights: A homogeneous thiol and pH dual-response cathodic ECL sensor was first developed. It efficiently avoided electrode's modification and pigment's spectral interference. This ECL sensor achieved highly sensitive analysis of target OP at 0.016 ng/mL. It also displayed good practicability to detect methidathion in Chinese cabbage. Abstract: Electrochemiluminescent (ECL) sensors for organophosphorus pesticides (OPs) have received considerable attention, whereas complicated electrode's immobilization, response to single hydrolysate and anodic emission correlated with ECL assays restrict their potential utilization. Herein, we developed a homogeneous dual-response cathodic ECL system for highly sensitive and reliable analysis of OP using CdTe QDs as emitters. CdTe QDs, emitting red light, were fabricated through a hydrothermal reaction and generated anodic and cathodic ECL emission upon stimulation of tripropyl amine and K2 S2 O8, respectively. Notably, CdTe QDs-K2 S2 O8 showed a simultaneous response to thiol and acidic pH, and were regarded as a ECL sensor for methidathion with limit of detection of 0.016 ng/mL based on hydrolysis of acetylthiocholine into thiocholine and CH3 COOH by acetylcholinesterase (AChE) and OPs' inhibition on AChE activity. This sensor also exhibited good practicability to detect methidathion in Chinese cabbage. Overall, the sensor will supply more useful information for ensuring OPs-related food safety.